Noninvasive Management of an Odontoid Process Fracture in a Toddler: Case Report. (February 2015) - Kim, Woosung; O'Malley, Mike; Kieser, David Christopher
Study Design: Case report. Objective: Odontoid process fractures represent an uncommon injury in small children, with their optimal management remaining unclear. We present a case of conservatively managed displaced type 2 odontoid process fracture in a small child. Methods: We analyzed clinical and radiographic outcomes of a restrained 2-year-old girl involved in a motor vehicle accident who sustained a displaced type 2 odontoid process fracture and was treated conservatively in a semirigid Aspen collar. Results: The fracture progressively healed with callus formation evident at 6 weeks. By 12 weeks, the patient was asymptomatic and had regained head control and a full range of movement. Radiographic remodeling of the fracture was seen to improve over the 6-month follow-up. Conclusion: This case illustrates that displaced type 2 odontoid process fractures can be successfully managed conservatively in small children.